Beneath the surface: Navigating engagement model in the women’s rights communication of Philippine Alliances of Human Rights Association (PAHRA) - Chen, Katherine C. (Animo Repository, 2023)
This production thesis study applied Dhanesh's (2017) engagement model in investigating how engagement is facilitated in the Philippine Alliance of Human Rights Advocates (PAHRA), a non-profit organization based in Manila, Philippines, that advocates for championing human rights. This study explored PAHRA’s notions of engagement, particularly in its women’s rights advocacy context, from its communicative practices, efforts, and processes. The researchers conducted a semi-structured interview to gather data and thematic analysis to find common themes among PAHRA’s National Executive Congress (n=6) and one focus group discussion with PAHRA’s public with experience with the organization (n=4). This study extended literature on the engagement model as a framework and practice of organizational communication. Furthermore, this study argued that organizations must have further knowledge in improving their strategic communication in pursuit of practicing and communicating with the public, particularly with the help of the engagement model, to facilitate effective engagement. Given the results of the study, a social media playbook grounded on Dhanesh's (2017) states and model of engagement was produced and consisted of (a) content strategy, (b) content checklist and guidelines, (c) copywriting guide, (d) and social media templates (e.g., stories, postings, hashtags, and a templated content calendar plan). Keywords: Engagement Model, Public Relations, Philippine Organizations, Women’s Rights, Organizational Communication